دلائل نبوت:مفہوم اقسام اور مترادفات: Proofs of Prophethood, Concept, types and Synonyms - Dr. Asma Aziz,; Kadija Shoukat,; Farzana Hameed, (Al Manhal Research Journal, 2024)
Allah sent His messengers one after the other for the guidance of mankind. This series started with Hazrat Adam (AS) and completed with our Last Prophet Hazrat Muhammad (PBUH). Whenever a prophet deputed by Allah to guide any nation, that nation asked for proofs on the truth of the Prophet's prophet hood and also demanded the miracles. With Allah’s help, every prophet displayed some miracles to his nation to prove his righteousness or prophethood. This display of miracles turned many people to Allah, but there were still many unfortunate ones who did not embrace Allah’s path even after that. Evidences of prophet hood have been appearing in every age. The question is, what are the Dalil-e-Nabuwah (proofs of prophecy) and through which ways these can be effectively used to convince people? This research is a discussion on dissemination of all these evidences to the world in form of Qura’anic verses, words in other Holy Scriptures, miracles of the Prophet(PBUH), his life history, his Seerah, his prophecies, and all his prayers accepted by Allah the Almighty. Renowned international biographers and muhaddithin have written exclusive chapters on proofs on the truth of the Prophet's prophet hood. They consider it to be one of very important aspects of the biography of the Holy Prophet (PBUH). The debate of Proofs of Prophethood is very unique and important in the field of Seerah, Ilm ul Klam as well. Famous scholars worked on it primary subjects i.e. definition of Dail un Nabwah, its literal and terminological meanings, its synonym word, its types that how autobiographers, Muhaditheen and Mutakalmeen discuss and enlights and necessity of Prophethood. This research deals with all its scholarly debates to unveil this part of Seerah and Ilm ul Kalam.